Does better availability mean better accessibility? Spatial inequalities in the care of acute myocardial infarction in Hungary - Uzzoli, Annamária; Egri, Zoltán; Szilágyi, Dániel; Pál, Viktor (Hungarian Geographical Bulletin, 2020)
The availability of health care services is an important issue, however, improving availability of health care services does not necessarily mean better accessibility for everybody. The main aim of this study is to find out how better availability in the care of acute myocardial infarction vary with accessibility of patients’ geographical location within Hungary. We applied statistical analysis and interview techniques to unfold the role of spatiality in the conditions of access to health care. Results of statistical analysis indicate significant health inequalities in Hungary. Decreasing national mortality rates of acute myocardial infarction, has been coupled by increasing spatial inequalities within the country especially at micro-regional level. According to in-depth interviews with local health care stakeholders we defined factors that support access to health care as well as important barriers.The supporting factors are related to the improvement of availability (i.e. infrastructural developments), while geographical distance, lack of material and human resources, or low level of health literacy proved to be the most relevant barriers. Main conclusion is that barriers to accessibility and availability are not only spatial but are also based on individual stages of acute myocardial infarction care. The development of cardiac catheter centres in Hungary has improved the short-term chances of infarction survival, but long-term survival chances have worsened in recent years due to deficiencies in rehabilitation care as well as low level of health literacy.